Cerebral Microbleeds, Cerebral Amyloid Angiopathy, and Their Relationships to Quantitative Markers of Neurodegeneration. (19th April 2022) - Beaman, Charles; Kozii, Krystyna; Hilal, Saima; Liu, Minghua; Spagnolo-Allende, Anthony J.; Polanco-Serra, Guillermo; Chen, Christopher; Cheng, Ching-Yu; Zambrano, Daniela; Arikan, Burak; Del Brutto, Victor J.; Wright, Clinton; et al.
Abstract : Background and Objectives: Age-related cognitive impairment is driven by the complex interplay of neurovascular and neurodegenerative disease. There is a strong relationship between cerebral microbleeds (CMBs), cerebral amyloid angiopathy (CAA), and the cognitive decline observed in conditions such as Alzheimer disease. However, in the early, preclinical phase of cognitive impairment, the extent to which CMBs and underlying CAA affect volumetric changes in the brain related to neurodegenerative disease remains unclear. Methods: We performed cross-sectional analyses from 3 large cohorts: The Northern Manhattan Study (NOMAS), Alzheimer's Disease Neuroimaging Initiative (ADNI), and the Epidemiology of Dementia in Singapore study (EDIS). We conducted a confirmatory analysis of 82 autopsied cases from the Brain Arterial Remodeling Study (BARS). We implemented multivariate regression analyses to study the association between 2 related markers of cerebrovascular disease—MRI-based CMBs and autopsy-based CAA—as independent variables and volumetric markers of neurodegeneration as dependent variables. NOMAS included mostly dementia-free participants age 55 years or older from northern Manhattan. ADNI included participants living in the United States age 55–90 years with a range of cognitive status. EDIS included community-based participants living in Singapore age 60 years and older with a range of cognitive status. BARS included postmortem pathologic samples. Results: We included 2, 657 participants with available MRI data and 82 autopsy cases from BARS. In a meta-analysis of NOMAS, ADNI, and EDIS, superficial CMBs were associated with larger gray matter (β = 4.49 ± 1.13, p = 0.04) and white matter (β = 4.72 ± 2.1, p = 0.03) volumes. The association between superficial CMBs and larger white matter volume was more evident in participants with 1 CMB (β = 5.17 ± 2.47, p = 0.04) than in those with ≥2 CMBs (β = 1.97 ± 3.41, p = 0.56). In BARS, CAA was associated with increased cortical thickness (β = 6.5 ± 2.3, p = 0.016) but not with increased brain weight (β = 1.54 ± 1.29, p = 0.26). Discussion: Superficial CMBs are associated with larger morphometric brain measures, specifically white matter volume. This association is strongest in brains with fewer CMBs, suggesting that the CMB/CAA contribution to neurodegeneration may not relate to tissue loss, at least in early stages of disease.